Scaling up sustainability through new product categories and certification: Two cases from India - Khandelwal, Apoorve; Agarwal, Nandini; Jain, Bhamini; Gupta, Darshna; John, Anjaly Teresa; Farah Cox, Paul (Frontiers in Sustainable Food Systems, 2022)
The Indian food system faces a nexus of challenges in supply, demand and market linkages in the face of environmental and human development needs. The current agri-food system demands large-scale sustainable innovations, facilitated by an action-oriented approach by the rising number of actors in the agricultural space. These actors include public, private, non-profit and research institutions. They increase the scope for innovations to emerge and scale up through refocused investments and novel collaborations. Such successes in India, furthermore, can provide models of promising innovation pathways for many other countries in the Global South. Yet few case studies are available on successful innovations that have gone beyond the longstanding technology-led approach. This article presents two cases of other pathways. The first is an example of a differentiated new product category: the “pesticide-free” food product category and dedicated value chain established by Safe Harvest Private Limited. The second is an example of self-regulation through a certification standard: the Trustea code created within the Indian domestic tea industry. Both are driving sustainability at scale in Indian agri-food systems in two very different contexts, with the private sector leading the way. They offer insights on the roles of end users, trust, informal and formal links and actions, government endorsement, innovation bundling, and partnership.